A Study of Software Implemented Fault Tolerance in AUTOSAR Based Systems - Kumar Shovan, Paul; Dewan Sarwar, Mahabub (My University, 2013)
The AUTOSAR standard simplifies the complexity of automotive system design with its layered and modular software architecture. Currently, this standard has no support for fault-tolerance. Fault-tolerance will be required in the design of the future automotive systems to avoid catastrophic system failures and hazardous events. In this thesis, we present a study of fault-tolerance by means of software in AUTOSAR based systems. The aim of the study is to investigate how fault-tolerance mechanisms can be implemented in AUTOSAR. To this end, we implemented duplication and comparison, and triple modular redundancy in AUTOSAR in order to investigate how errors can be detected and fault-tolerance can be achieved, respectively. Moreover, the study focuses on the implementation of the distributed consensus protocol to investigate the impact of fault-tolerance in distributed scenario. In addition, we measure the timing overhead of the consensus protocol in which we observe that the execution-time declines with the increasing number of joining nodes.
Keywords: Data- och informationsvetenskap; Computer and Information Science